Air Quality Assessment Standards and Sustainable Development in Developing Countries - Yuan, Guanghui (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book brings together the latest research results of air quality assessment standards and sustainable development in developing countries. The content is full and the discussion is vivid. These articles are suitable for students and researchers at all levels seeking to understand the status of air pollution, governance standards, and governance effects in developing countries.